Interspecific and Intergeneric Hybrids of Aerides Species with Rhynchostylis coelestis Rchb.f. and Germination of Hybrid Seeds In Vitro - Jitsopakul, Nipawan; Chunthaworn, Atcharaporn; Pongket, Urailuck; Thammasiri, Kanchit (Trends in Sciences, 2022)
The beautiful Thai orchid species are Aerides and Rhynchostylis coelestis Rchb.f. that hybrids are valued for potted plants or cut flowers. Interspecific hybridization of Aerides species and intergeneric hybridization of Aerides species with Rhynchodtylis coelestis were investigated to observe their cross ability and the germination of hybrid seeds in vitro. The successful crosses were 4 interspecific hybrids including A. multiflora × A. houlletiana, A. odoratum × A. multiflora, A. odoratum × A. houlletiana, A. falcata × A. houlletiana (40 to 100 % pod formation) and 3 intergeneric hybrids including A. multiflora × R. coelestis, A. houlletiana × R. coelestis and A. falcata × R. coelestis (83 to 100 % pod formation). The age and size of mature pods of interspecific hybrids were 106 to 181 days with length of 1.40 to 2.37 cm and width of 0.70 to 1.23 cm and intergeneric hybrids were 93 to 165 days with length of 1.75 to 2.68 cm and width of 0.81 to 1.18 cm after pollination. Seeds of 4 interspecific and 3 intergeneric hybrids germinated into protocorms after sowing on VW (1949) agar medium for 26 to 84 days and 35 to 50 days, respectively. Hybrid plantlets with well-developed shoots and roots for 150 days after cultured on modified VW (1949) agar medium supplemented with 100 g L–1 banana, 150 mL L–1 coconut water, 20 g L–1 sucrose, 2 g L–1 activated charcoal, 7 g L–1 agar, and pH 5.2 at 25 ± 2 °C under light condition for 16 h day–1. Hybrid plantlets were transplanted into greenhouse condition after 180 days showed 100 % survival and grew. The successful hybridization of Aerides hybrids can be applied for production new varieties of orchids. HIGHLIGHTS The genus Aerides is one of the most beautiful Thai orchids that flowers have variation in shapes, sizes, and color for potted plants or cut flowers. Rhynchostylis coelestisf. is native to Thailand that the flower colors are purple used for trades and making hybrids There are reported on interspecific hybridization of some Aerides without intergeneric hybridization with Rhynchostylis coelestis Rchb.f The ability to interspecific hybridization of Aerides and intergeneric hybridization between Aerides spp. with Rhynchostylis coelestis Rchb.f. were successful for pod formation, seed germination and developed into plantlets GRAPHICAL ABSTRACT